PANCASILA DI ERA PASKA IDEOLOGI - Dwi Putro, Widodo (Veritas et Justitia, 2019)
It is considered axiomatic that Pancasila has been accepted as State ideology (formally and final) and in addition been perceived as the ultimate source of all legal sources. But this acceptance as axiom leads to the fact that Pancasila has almost never been reflected upon. This said in consideration that the basis for this ideology, the contemporary society tends to be suspicious of ideology or grand narratives.  This article, as a reflective-critical analysis, shall discuss how Pancasila is understood by the Indonesian post ideological society. The critiques put forward is meant to offer an alternative value transformation for a society disillusioned by grand narratives.